IMPACT OF PROTEIN AND MINERAL SUPPLEMENTATION DURING TRANSITION PERIOD ON PUERPERAL EVENTS AND POSTPARTUM FERTILITY IN BUFFALOES - KALASARIYA, R M; DHAMI, A J; HADIYA, K.K.; PATEL, j j (The Indian Journal of Animal Reproduction, 2015)
Eighty-five advanced pregnant (~8 mo) pluriparous buffaloes at farmer’s doorstep in tribal villages were selected and randomly divided into basal feeding (n=45, routine feeding by farmer) and basal + supplemental feeding (n=40, daily 1.5 kg concentrate mixture and 50 g chelated Area Specific Mineral Mixture) groups. The buffaloes received supplemental feeding for two months each pre- and post-partum. In addition, 15 buffalo of each group received injectable micro-mineral (5 ml, i.m.; each ml containing Se, Zn, Cu and Mn @ 5, 40, 15 and 10 mg, respectively) about two month before calving and on the day of calving. The micro-mineral injection appreciably reduced the incidence of retained placenta (p>0.05) as well as the placenta expulsion time (p0.05) in basal fed group compared to supplemented buffalo. Also, the interval to first postpartum estrus and service period were shorter with higher conception rate and lesser number of services per conception in supplemented buffalo than in buffalo reared on basal feeding (p0.05). Injectable micro-mineral further improved all these traits in both the groups (p0.05). Overall subfertility in terms of true anestrus, subestrus and repeat breeding was reduced in supplemented buffalo compared to basal fed buffalo (p>0.05). In brief, nutrient supplementation in terms of high protein concentrate and minerals (oral + injectable) during transition period prevented periparturient complications and improved the postpartum reproductive performance in buffalo under field conditions.
Keywords: Buffalo; Transition period; Nutritional supplementation; Postpartum fertility; Puerperal disorders